MODEL PEMBELAJARAN FLIPPED CLASSROOM SEBAGAI UPAYA PENINGKATAN KEMAMPUAN PENGUASAAN RUMUS TRANSFORMASI GEOMETRI - Muhammad Abidin (Universitas Sulawesi Barat, 2019)
This is a classroom based action research to improve students’ ability in mastering geometry transformation formula through flipped classroom learning model. The study lasted for two cycles and conducted in class XII IPA 1 SMA Negeri 2 Barru. There were 25 students as participants for this study. The first cycle shows that 52% students have enough skil in mastering geometry transformation formula.Clasically, it can be seen that the average students score is 71,92 which is below the minimal score standard. The second cycle shows a better result that 80% students obtain a very high ability in mastering geometry transformation formula. Clasically, the average score of students in the second cycle is 90,80 which is above the minimal score standard. Based on the result of the students XII IPA 1 final evaluation, it is showing that the students ability to master geometry transformation formula is 90,80%. Besides, 100% of the students obtain score ≥ 75. Based on the result of this study, it can be concluded that there is an increase of students’ ability in mastering geometry transformation formula through flipped classroom. In addition, the study also obtained that flipped classroom increases students motivation and activeness in the classroom.